Processing Trash Fish into Economically Valuable Animal Feed in Nagari Pilubang, Padang Pariaman Regency - Sari, Trisna Kumala; Away, Romy Dwipa Yamesa; Suryani, Okta; Yeni, Isra; Aini, Syamsi; Kurniawati, Desy; Nasra, Edi; Stiadi, Della Rosalynna (Pelita Eksakta, 2024)
There has been concealed on the processing of trash fish into animal feed in Nagari Pilubang, Padang Pariaman Regency. The majority of the Pilubang community are fishermen. However, so far the trash fish caught have not been processed properly. Meanwhile, trash fish has the potential to be used as animal feed because it contains high protein. Through this PKM activity, the community receives education and training regarding the application of technology for processing trash fish into animal feed using appropriate technology. The animal feed was made from trash fish is processed using a fermentation process. From the results of this activity, it is known that community knowledge has increased and is very useful for implementation by the community in Nagari Pilubang